ANALISIS PREDIKSI KEBANGKRUTAN DENGAN METODE ALTMAN Z-SCORE PADA PERUSAHAAN TELEKOMUNIKASI GO PUBLIC YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2010 - 2014 - Untung Sriwidodo, Imam Suherman, Edi Wibowo (Universitas Slamet Riyadi, 2016)
Financial reports are one source of information that can be used to determine a company's financial position, performance and assist in making the right decision. This study aims to determine the use of methods of Altman Z-score in predicting corporate bankruptcies in Indonesia by using the data in the form of financial statements balance sheet and income statement of the company. Research method used is by using the method of Altman Z-Score that connects the five variables representing liquidity ratio (X1), Profitability (X2 and X3), Activity (X4 and X5). Z-Score formula = 1,2 X1 + 1,4 X2 + 3,3 X3 + 0,6 X4 + 1,0 X5. With criterion Z-Score > 2,99 categorized as a very healthy company. 1,81 < Z-Score < 2,99 are in the grey area so the chances saved and the possibility of bankruptcy as much depend on the company’s management policy decision as decision makers. Z-Score < 1,81 is categorized as a company that has a very large financial difficult and high risk so that huge downfall of possibilities.Keywords: Analysis of bankruptcy, Altman Z-Score model, Telecommunications company in Indonesia Stock Exchange